The Economic Analysis of Women Employee Contributions and Time Devotion in Kota Jati Furindo LLC - Dewi Amira Eka Nugraha; Nuriah Yuliati; Mubarokah Mubarokah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
This research was conducted in 2025 with the aim of analyzing economic contributions and the time devotion at Kota Jati Furindo LLC dedicated to supporting their family economy and analyzing their contributions. The study was conducted at Kota Jati Furindo LLC, situated on the Jepara-Bangsri road, approximately 6.5 kilometers from Jepara, Central Java, Indonesia. The company operates in the timber industry and employs a significant number of women, particularly in the production department. This study used the census method for data collection, chosen because it allows the inclusion of the entire population that meets the criteria as respondents, resulting in more accurate findings. The study involved 50 respondents, specifically married women employees working in the packing and sanding divisions. Data were collected through a structured questionnaire and analyzed using appropriate statistical methods. The study employed descriptive analysis with a quantitative approach for data analysis. This approach was chosen to provide an in-depth understanding of the time dedication and economic contribution of the respondents. The data analysis showed that women employees at Kota Jati Furindo LLC spend an average of 33.33% of their time each week on economic activities or work. Meanwhile, the average time spent on non-economic activities, such as attending to personal needs, social activities, and household chores, was 66.65% per week. The contribution analysis revealed that the economic contribution of women employees to the family income is 43%, which falls into the medium category. Policy implications based on these findings suggest that the company needs to develop policies that support a better work-life balance for its female employees. For example, offering more flexible work arrangements or improved leave policies could help women manage the time between work and family responsibilities, thus enhancing their economic contribution more optimally.